A heuristic job-shop scheduling algorithm to minimize the total holding cost of completed and in-process products subject to no tardy jobs - Ohta, Hiroshi; Nakatani, Toshihiro (International journal of production economics, 2006)
Meeting due dates is the most important goal of scheduling if the due date of each job has been promised to its customer. This paper considers the job-shop scheduling problem of minimizing the total holding cost of completed and in-process products subject to no tardy jobs. A heuristic algorithm based on the shifting bottleneck procedure is proposed for solving the minimum total holding cost problem subject to no tardy jobs. Several benchmark problems which are commonly used for job-shop scheduling problems of minimizing the makespan are solved by the proposed method and the results are reported.